Knowledge Unbound Selected Writings on Open Access, 2002-2011 - Suber, Peter (The MIT Press, 2016)
Influential writings make the case for open access to research, explore its implications, and document the early struggles and successes of the open access movement. Peter Suber has been a leading advocate for open access since 2001 and has worked full time on issues of open access since 2003. As a professor of philosophy during the early days of the internet, he realized its power and potential as a medium for scholarship. As he writes now, "it was like an asteroid crash, fundamentally changing the environment, challenging dinosaurs to adapt, and challenging all of us to figure out whether we were dinosaurs." When Suber began putting his writings and course materials online for anyone to use for any purpose, he soon experienced the benefits of that wider exposure. In 2001, he started a newsletter-the Free Online Scholarship Newsletter, which later became the SPARC Open Access Newsletter-in which he explored the implications of open access for research and scholarship. This book offers a selection of some of Suber's most significant and influential writings on open access from 2002 to 2010. In these texts, Suber makes the case for open access to research; answers common questions, objections, and misunderstandings; analyzes policy issues; and documents the growth and evolution of open access during its most critical early decade.